2014
DOI: 10.3109/00016489.2014.940556
|View full text |Cite
|
Sign up to set email alerts
|

The dominant foot affects the postural control mechanism: examination by body tracking test

Abstract: ConclusionThe antero-posterior (AP) body tracking test (BTT) showed that the dominant foot could affect the tilt angle of the sway movement, delineated by primary component analysis. Differences associated with the dominant foot could represent the difference in space perception of each person.ObjectivesTo examine whether the dominant foot could affect the postural control mechanism using the BTT. MethodsNinety-seven healthy participants enrolled in the study were classified into right-foot and left-foot domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Asymmetrical distribution of weight through the LEs found in both the patient and control groups might be due to the dominant foot entity. A previous study demonstrated that foot dominance and postural control have a correlation, 20 and this finding is consistent with the data of this study.…”
Section: Discussionsupporting
confidence: 93%
“…Asymmetrical distribution of weight through the LEs found in both the patient and control groups might be due to the dominant foot entity. A previous study demonstrated that foot dominance and postural control have a correlation, 20 and this finding is consistent with the data of this study.…”
Section: Discussionsupporting
confidence: 93%
“…Traditionally, studies on footedness analyzed unipedal postural stability by assessing the center of pressure (COP) oscillations; however, the COP-based variables, such as sway area [16], COP excursion [17], 95% COP elliptical area [18], standard deviation [18], total path length [16,18], and speed [8,18], did not indicate an effect of leg dominance. Only in a body-tracking test [19] were effects of footedness observed when participants received visual feedback of their performance. Visual feedback might make a difference, since processing visual information is also distributed asymmetrically between the brain hemispheres [20,21], which could interact with neural asymmetries, causing motor control laterality.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, our study result indicates the importance of the TGF of the DF for preventing falls. Yoshida et al [ 10 , 11 ] reported that the DF may contribute to spatial perception in standing posture control and posture control mechanism in dynamic balance. Furthermore, Demura et al [ 21 ] reported that, compared with the non-DF, the DF was superior in its ability to regulate muscle exertion.…”
Section: Discussionmentioning
confidence: 99%
“…Dominance is defined as a phenomenon in which one side of the left-right pair of body parts, such as the hands and feet, shows better results in cognitive and motor tasks than the other side [ 8 , 9 ]. Yoshida et al [ 10 , 11 ] reported that the function of the dominant foot (DF) may affect standing posture control in dynamic balance. Based on these reports, it is necessary to pay attention to the function of the DF.…”
Section: Introductionmentioning
confidence: 99%